Application of Synchrotron Radiation‐based Methods for Environmental Biogeochemistry: Introduction to the Special Section. Issue 6 (1st November 2017) - Hettiarachchi, Ganga M.; Donner, Erica; Doelsch, Emmanuel
Abstract : To understand the biogeochemistry of nutrients and contaminants in environmental media, their speciation and behavior under different conditions and at multiple scales must be determined. Synchrotron radiation‐based X‐ray techniques allow scientists to elucidate the underlying mechanisms responsible for nutrient and contaminant mobility, bioavailability, and behavior. The continuous improvement of synchrotron light sources and X‐ray beamlines around the world has led to a profound transformation in the field of environmental biogeochemistry and, subsequently, to significant scientific breakthroughs. Following this introductory paper, this special collection includes 10 papers that either present targeted reviews of recent advancements in spectroscopic methods that are applicable to environmental biogeochemistry or describe original research studies conducted on complex environmental samples that have been significantly enhanced by incorporating synchrotron radiation‐based X‐ray technique(s). We believe that the current focus on improving the speciation of ultra‐dilute elements in environmental media through the ongoing optimization of synchrotron technologies (e.g., brighter light sources, improved monochromators, more efficient detectors) will help to significantly push back the frontiers of environmental biogeochemistry research. As many of the relevant techniques produce extremely large datasets, we also identify ongoing improvements in data processing and analysis (e.g., software improvements and harmonization of analytical methods) as a significant requirement for environmental biogeochemists to maximize the information that can be gained using these powerful tools. Core Ideas: SR‐based techniques have revolutionized the field of environmental biogeochemistry. Improvements to light sources will provide SR with extreme brightness and coherence. This should be met with similar advances to synchrotron‐related hardware and software. Environmental biogeochemists can drive the new advances in the synchrotron science. Advances in SR will enable future breakthroughs in environmental biogeochemistry.